Carvacrol exerts nephroprotective effect in rat model of diclofenac-induced renal injury through regulation of oxidative stress and suppression of inflammatory response. Issue 11 (November 2021) - Nouri, Ali; Izak-Shirian, Farzad; Fanaei, Vahideh; Dastan, Maryam; Abolfathi, Mahdieh; Moradi, Alireza; Khaledi, Mansoor; Mirshekari-Jahangiri, Hamzeh
Abstract: Diclofenac (DIC) is an NSAID that can cause toxic effects in animals and humans and carvacrol (CAR) is a monoterpene compound that displays effective pharmacological and biological actions. The purpose of this work was to assess the influences of CAR on DIC-induced renal injury and oxidative stress in male rats. The rats were segregated into four groups. Group 1, control group; Group 2 received DIC-only; Groups 3, received CAR-only and group 4 received DIC plus CAR. Changes in biochemical indexes, pathological changes, molecular biological indexes, and genes related to the inflammation of main organs were evaluated. The results of this work indicated that the amounts of the serum protein carbonyl, sGOT, sGPT, urea, creatinine, uric acid, nitrite content, MDA, serum TNF-α, and renal TNF-α gene expression were remarkably increased and the levels of the GPx, GSH, CAT, and SOD were significantly reduced in DIC-only treated animals compared to the control group. On the other hand, treatment with CAR after exposure to DIC led to significant improvements in abnormalities of DIC-induced renal injury and serum biochemical factors. The data approve that CAR diminished the deleterious effects of DIC exposure. In this regard, the findings of this study indicated that the administration of CAR could alleviate the noxious effects of DIC on the antioxidant defense system and renal tissue. Abstract : Carvacrol; Diclofenac; Oxidative stress; DIC-induced renal injury. Graphical abstract: Image 1